2002
DOI: 10.1034/j.1399-3054.2002.1150216.x
|View full text |Cite
|
Sign up to set email alerts
|

Auxin stimulates S6 ribosomal protein phosphorylation in maize thereby affecting protein synthesis regulation

Abstract: Auxin is known to stimulate protein synthesis in many plant tissues, but the mechanisms involved in this process are unknown. The present research inquires whether auxin might regulate selective translation of mRNAs by inducing S6 ribosomal protein phosphorylation on the 40S ribosomal subunit in maize (Zea mays L.). Maize embryonic axes auxin-stimulated by natural (IAA) or synthetic (Dicamba or 1-NAA) auxins, selectively increased ribosomal protein synthesis. This effect was not reproduced by auxin inactive an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 48 publications
1
33
0
2
Order By: Relevance
“…It is thus tempting to hypothesize that TOR has been recruited in plants to regulate specifically in leaves the translation of nuclear mRNAs coding for chloroplastic ribosomal proteins. It was previously shown that translation of animal TOP-containing mRNAs can be differentially regulated in vitro in a wheat germ extract (Shama and Meyuhas, 1996) and that auxin stimulates S6 ribosomal protein phosphorylation on maize ribosomes and the recruitment of TOP-like mRNAs for translation (Beltrán-Peña et al, 2002). Since TOR is also activated by auxin (Schepetilnikov et al, 2013) these data suggest that plant mRNAs containing TOP-related motifs could also be regulated in a TOR- and phosphorylated S6-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…It is thus tempting to hypothesize that TOR has been recruited in plants to regulate specifically in leaves the translation of nuclear mRNAs coding for chloroplastic ribosomal proteins. It was previously shown that translation of animal TOP-containing mRNAs can be differentially regulated in vitro in a wheat germ extract (Shama and Meyuhas, 1996) and that auxin stimulates S6 ribosomal protein phosphorylation on maize ribosomes and the recruitment of TOP-like mRNAs for translation (Beltrán-Peña et al, 2002). Since TOR is also activated by auxin (Schepetilnikov et al, 2013) these data suggest that plant mRNAs containing TOP-related motifs could also be regulated in a TOR- and phosphorylated S6-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…In Arabidopsis, RPS6 phosphorylation is promoted during the day (Turkina et al, 2011;Boex-Fontvieille et al, 2013) and in response to auxin and cytokinin (Turck et al, 2004), but is repressed by hypoxia . In monocots, RPS6 is phosphorylated in embryos during germination (Beltrán-Peña et al, 2002) and its phosphorylation rapidly declines following hypoxia, heat shock and singlet oxygen treatment (Williams et al, 2003;Khandal et al, 2009). The RPS6 kinase of Arabidopsis, AtS6K1, is important in regulating cell division and growth (Henriques et al, 2010;Shin et al, 2012).…”
Section: Ribosomal Protein Phosphorylationmentioning
confidence: 99%
“…Several ribosomal proteins have been associated with auxin-related developmental processes, such as cell proliferation, cell expansion, and polarity establishment in leaves (39)(40)(41). Auxins also trigger the coordinate expression of ribosomal protein mRNAs (55,56), increase de novo ribosomal protein synthesis (57), and change ribosomal protein phosphorylation patterns (58,59). In our study, mutations in multiple ribosomal genes caused specific auxin-related defects rather than a nonspecific defect in translation.…”
Section: Arf3 Uorfs Are Partially Responsible For Several Auxin-relatedmentioning
confidence: 99%